2021
DOI: 10.1371/journal.pone.0256965
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of interactional and organizational determinants of collaboration in cancer palliative care settings: Family members’, health care professionals’ and key informants’ perspectives

Abstract: As life expectancy has increased, a growing number of people experience conditions, including cancers, that carry complex health and social needs. Palliative care services have the potential to address these needs but face significant obstacles. One major obstacle is suboptimal interprofessional collaboration. This study’s goal was an in-depth exploration of interactional and organizational barriers and supports of collaboration in palliative care in Switzerland. We sought the perspectives of health care profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…The lack of collaboration, coordination, and communication between sectors and within individual sectors has repeatedly been identified as a barrier to palliative care. 7,8 A Norwegian study identified three main barriers experienced by district nurses and GPs. 9 The first was the lack of an initial interdisciplinary meeting to ensure coordination of palliative care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of collaboration, coordination, and communication between sectors and within individual sectors has repeatedly been identified as a barrier to palliative care. 7,8 A Norwegian study identified three main barriers experienced by district nurses and GPs. 9 The first was the lack of an initial interdisciplinary meeting to ensure coordination of palliative care.…”
Section: Introductionmentioning
confidence: 99%
“…The Danish NG on palliative care recommends systematic needs assessment, planning and initiation of services based on patient needs, collaboration across healthcare sectors and between general and specialised palliative care providers such as the hospital department, municipalities, and patients' general practitioners (GPs), implementation, and follow‐up 4 (Appendix). The lack of collaboration, coordination, and communication between sectors and within individual sectors has repeatedly been identified as a barrier to palliative care 7,8 . A Norwegian study identified three main barriers experienced by district nurses and GPs 9 .…”
Section: Introductionmentioning
confidence: 99%